معيقات تطبيق الرقمنة بالادارات العمومية الجزائرية - رميسة كميتي; د/ مباركة رحماني (جامعة عمار ثليجي بالاغواط, 2025)
ملخص الدراسة : ملخص الدراسة تتناول هذه الدراسة موضوع معيقات تطبيق الرقمنة في الإدارات العمومية الجزائرية، من خلال تحليل واقع التحول الرقمي وأهم التحديات البنيوية والتنظيمية التي تعيقه. وتهدف إلى إبراز أثر عوامل مثل ضعف البنية التحتية، نقص التكوين، غياب التنسيق، ومحدودية الموارد على فعالية الرقمنة. كما تستعرض تطور الرقمنة في الجزائر، ووظائف الإدارة العمومية، ومظاهر الرقمنة داخلها، لتخلص إلى ضرورة اعتماد رؤية استراتيجية شاملة تعزز البيئة الرقمية وتحسن جودة الخدمة العمومية. الكلمات المفتاحية: الرقمنة، الإدارة العمومية، الجزائر، معيقات التحول الرقمي، البنية التحتية، . Abstract : This study addresses the issue of obstacles to the implementation of digitization in Algerian public administrations, by analyzing the current state of digital transformation and the main structural and organizational challenges it faces. The objective is to highlight the impact of factors such as weak infrastructure, lack of training, poor coordination, and limited resources on the effectiveness of digitization. The study also explores the evolution of digitization in Algeria, the functions of public administration, and digital practices within it. It concludes by emphasizing the need for a comprehensive strategic vision to strengthen the digital environment and improve public service quality. Keywords: Digitization, Public Administration, Algeria, Digital Transformation Barriers, Infrastructure,
دراسة ميدانية على عينة من الادارات العمومية بولاية الاغواط